2004
DOI: 10.1183/09031936.04.00122903
|View full text |Cite
|
Sign up to set email alerts
|

Clonal strains ofPseudomonas aeruginosain paediatric and adult cystic fibrosis units

Abstract: Despite recent reports of clonal strains of Pseudomonas aeruginosa in cystic fibrosis (CF) units, the need for routine microbiological surveillance remains contentious.Sputum was collected prospectively from productive patients attending the regional paediatric and adult CF units in Brisbane, Australia. All P. aeruginosa isolates were typed using pulsed-field gel electrophoresis. Spirometry, anthropometrics, hospitalisations and antibiotic sensitivity data were recorded.The first 100 sputum samples (first 50 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
96
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 31 publications
9
96
1
Order By: Relevance
“…However, multiple reports from the UK, Australia and Norway suggest that cross-infection between unrelated patients occurs much more frequently than previously recognised [3][4][5][6][7]10]. In keeping with the current findings, the studies from Liverpool, Melbourne, Brisbane and Bergen all found that the majority of P. aeruginosa-infected patients attending their centres harboured clonal isolates.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, multiple reports from the UK, Australia and Norway suggest that cross-infection between unrelated patients occurs much more frequently than previously recognised [3][4][5][6][7]10]. In keeping with the current findings, the studies from Liverpool, Melbourne, Brisbane and Bergen all found that the majority of P. aeruginosa-infected patients attending their centres harboured clonal isolates.…”
Section: Discussionsupporting
confidence: 75%
“…Although cross-infection with P. aeruginosa in siblings with CF is well documented [2], crossinfection in other settings has been thought to be rare. There is now increasing evidence of the importance of cross-infection in paediatric [3,4] and, more recently, adult [4][5][6][7] CF centres. There is naturally concern among patients, families and carers that this spread may adversely impact upon morbidity and mortality.…”
mentioning
confidence: 99%
“…51 Other reports described shared or epidemic P. aeruginosa strains in the United Kingdom and Australia. 53,[179][180][181] PFGE analysis of 1,225 P. aeruginosa isolates recovered from people with CF receiving care in 31 treatment centers in the United Kingdom demonstrated that 28% of those infected harbored a strain shared with at least 1 other person with CF. 173 The 2 most prevalent strains accounted for more than 20% of the isolates examined.…”
Section: Iiia2 P Aeruginosamentioning
confidence: 99%
“…Strain differences in the production of infectious droplets or droplet nuclei that remain suspended in the air under experimental conditions may explain the differences in efficiency of transmission of epidemic P. aeruginosa strains. 119 Infections with a shared strain 130,173,179 are highly suggestive of patient-to-patient transmission, particularly as institution of IP&C measures halted transmission. 30,185 While acquisition from a common source is also a possibility, surveillance of inpatient and outpatient settings have not detected a reservoir for shared strains.…”
Section: Iiia2 P Aeruginosamentioning
confidence: 99%
See 1 more Smart Citation